Implementación de métodos de procesamiento de señales EEG para aplicaciones de comunicación y control - Cordova Villar y Colls., Shirley (2018)
The Brain Computer Interface (BCI) is a communication instrument between mental or cognitive human function and the external environment, this mental function is created by the brain; the signals are captured, pre-processed and put into a classifier. This article aims to implement and compare the algorithms based on different methods of EEG signal processing for BCI applications that currently exist, in order to find methods whose algorithms provide better results.